2016
DOI: 10.1038/srep22500
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition and prefrontal hemodynamic responses during a working memory task in schizophrenia

Abstract: Social cognition is an important determinant of functional impairment in schizophrenia, but its relationship with the prefrontal functional abnormalities associated with the condition is still unclear. The present study aimed to explore the relationship between social cognition and prefrontal function in patients with schizophrenia using 52-channel near-infrared spectroscopy (NIRS). Twenty-six patients with schizophrenia and 26 age-, gender-, and intelligence quotient-matched healthy controls (HCs) participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
0
14
1
Order By: Relevance
“…Recent studies have assessed the neurocognitive domains together with the social cognitive domains in clinical rating scales, reporting mixed results regarding their link to brain structure and function 30 31 33 34 35 . Critically, none of these studies investigated the relationship of these 2 cognitive dimensions with brain structure and function independently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have assessed the neurocognitive domains together with the social cognitive domains in clinical rating scales, reporting mixed results regarding their link to brain structure and function 30 31 33 34 35 . Critically, none of these studies investigated the relationship of these 2 cognitive dimensions with brain structure and function independently.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent report has shown that ToM performance was significantly lower in patients with DLPFC damage than in their control group counterparts 47 . Thus, it seems reasonable to consider that DLPFC functioning is relevant to ToM performance, above and beyond its relevance to traditional working memory 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we observed for problem-oriented coping, this goes in the direction of a reversal of physiological restingstate network patterns. Frontopolar and temporal pole are indeed positively correlated structures of the DMN, whose local and synchronized activity has been related to theory of mind (Carrington & Bailey, 2009) and the processing of social interactions (Pu et al, 2016), with a focus on social rejection (Lee et al, 2014). Both of these elements might play roles when one considers seeking support.…”
Section: Resting-state Brain Connectivity and Copingmentioning
confidence: 95%
“…202 The lateral PFC HbO response in SZ patients was directly associated with theory-of-mind scores. 203…”
Section: N-back Taskmentioning
confidence: 99%